'What insights do fitness landscape models provide for theory and practice in public administration?'. Issue 7 (3rd July 2018) - Rhodes, Mary Lee; Dowling, Conor
ABSTRACT: This paper assesses the extent to which a fitness landscape (FL) perspective on complex social systems offers useful insights for both theory and practice in public administration. It has been claimed that FL models have strong potential for integrating existing theory and facilitating the development of models for theory development and testing as well as offering the prospect of a better understanding of  the adaptive moves of agents in search of a better 'fit' with their environment. In this paper, we examine these claims through a thematic synthesis of recent literature purporting to adopt this perspective in public management. Through a systematic review of the literature, we identify the key themes in the application of FLs to theory and practice and the extent to which authors are reaching any conclusions on the precise use of each of the elements of FL models in public management contexts. We conclude that the use of FL models is underdeveloped and that further development would be particularly useful in the context of governance network theory. We close with four specific recommendations for further research and development.